2017
DOI: 10.3390/ijms18081762
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia Iwayomogi Extract Attenuates High-Fat Diet-Induced Hypertriglyceridemia in Mice: Potential Involvement of the Adiponectin-AMPK Pathway and Very Low Density Lipoprotein Assembly in the Liver

Abstract: This study aimed to examine the protective effect of Artemisia iwayomogi extract (AI) against hypertriglyceridemia induced by a high-fat diet (HFD) in mice and to uncover the underlying molecular mechanisms. C57BL/6N mice were fed chow, HFD, HFD + 0.1% AI, HFD + 0.25% AI, or HFD + 0.5% AI for 10 weeks. The addition of 0.25% and 0.5% AI resulted in dose-dependent improvements in the major parameters of hypertriglyceridemia, including plasma triglyceride, free fatty acids, apolipoprotein B, and lipoprotein lipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In addition, HDL-C levels in the serum and liver were also affected with a moderate increase following long-term HFD feeding (P<0.05). Similar findings were also obtained in hypercholesterolemia mice fed a HFD [ 34 , 35 , 36 ]. However, although HDL-C increased with slightly statistical significance, the increasing fold of LDL-C was more obvious.…”
Section: Resultssupporting
confidence: 84%
“…In addition, HDL-C levels in the serum and liver were also affected with a moderate increase following long-term HFD feeding (P<0.05). Similar findings were also obtained in hypercholesterolemia mice fed a HFD [ 34 , 35 , 36 ]. However, although HDL-C increased with slightly statistical significance, the increasing fold of LDL-C was more obvious.…”
Section: Resultssupporting
confidence: 84%
“…To examine the underlying molecular mechanism, we examined the effect of SMSP supplementation on hepatic lipid metabolism such as lipogenesis and free fatty acid (FFA) oxidation. AMPK is one of the key activators of the lipogenesis and FFA oxidation catabolism [23]; we tested whether prolonged SMSP supplementation could modulate the AMPK pathways in the liver of alcohol-treated rats. Western blot results showed that SMSP administration significantly increased the phosphorylation of AMPK reduced by ethanol treatment.…”
Section: Smsp Supplementation Improves Lipid Metabolism In Ethanol-trmentioning
confidence: 99%
“…Mahmoodly [2] reported its significant use in African folk medicine. Indeed, Artemisia is known for its anti-inflammatory effects [3], hypocholesterolemia, and hypotriglyceridemia [4-7]. In folk medicine, in Kabyle region of Algeria, this grass is used to treat several symptoms such as digestive problems (diarrhea and stomach upset) and respiratory problems (bronchitis and cough).…”
Section: Introductionmentioning
confidence: 99%
“…In folk medicine, in Kabyle region of Algeria, this grass is used to treat several symptoms such as digestive problems (diarrhea and stomach upset) and respiratory problems (bronchitis and cough). Furthermore, antihelminthic and antileishmanial effects of Artemisia were reported in several studies [4,8-10].…”
Section: Introductionmentioning
confidence: 99%